Memorandum on social insurance and allied services in their bearing on neurotic disorder
1943 1943 1940s 19 pages 7 proper conditions, and its acceptance should not entail loss of self-respect or wastage of talent. (2) The initial choice should be the applicant's own, but it should be made only after he has been advised which of the available occupations might suit him and what each would entail, i.e. he should have the benefit of vocational guidance (often of a very simple kind). There should be the prospect of reasonable security of employment, and advancement if ambition is combined with abilities ; opportunity for a change after a reasonable trial, if dissatisfied, is essential. Unpleasant work should carry with it adequate compensatory advantages, rather than rely for its labour supply on the threat of unemployment or poverty. These stipulations would demand, on the part of the workers, a corresponding willingness to recognize that they must be ready to accept necessary restrictions, and changes, in the range of choice and location of work. Unless employment, and indeed society as a whole, is so organized that it provides other positive incentives to work besides the financial ones, there are grounds for the fears sometimes expressed that the Beveridge proposals might impair the desire to work. The training and rehabilitation schemes and the mechanism for finding employment should be planned with this, too, in view, e.g. those falling unemployed should be examined to find out why they are out of work. Regular machinery for analysing this information and methods of providing information on where employment is available or likely to become available are needed. If necessary, trained assistance from employment officers and suitably trained social workers should be available. Pay should be given during training, and not merely "sustenance" allowance. (d) Certain General Principles. Fairness and justice (both apparent and real), universality and comprehensiveness, simplicity and easy comprehensibility of the basic principles and procedure of the scheme are obvious requirements for any scheme which is going to impinge on all, and should receive high priority in its planning, provided only that none of its basic objectives are thereby impaired. The transparence of their relationship to the scheme should supersede the organization of its detail. They should supersede actuarial requirements and administrative difficulties wherever these conflict. Other general principles might perhaps be added to this list. The transitional provisions for old age can be criticized on these grounds, and also the poll-tax method of collection of payments. Clearly everyone should make a payment and recognize that he is doing so ; but a poll-tax method is not fundamental to this — in fact it might be argued that a tax partly proportional to income distributes the sense of responsibility more equally. Paranoid and other psychopathic attitudes may otherwise develop. (e) Certain other Social Objectives. The Report is patterned to encourage marriage, parenthood and the continuance at work of the able aged. These are desirable objectives, but measures 292/847/2/174